Analysis of Linen Management in Inpatient Room of X Hospital of Semarang City - Ririn Nurmandhani (Magister Kesehatan Masyarakat, Fakultas Kesehatan Masyarakat, Universitas Diponegoro, 2017)
Laundry unit is a non-medical support unit that provides linen services, especially for inpatient room. Based on the result from preliminary study, it is found that disarragement of linen management in Inpatient Room of X hospital Kota Semarang occured, which affected a logistic input, implementation, and logistic output. Analysis of linen management in inpatient room X Hospital Semarang is mandatory.The research design was qualitative with cross sectional approach. The main informants in this research were 4 laundry officers, Head of CSSD and Laundry, 2 nurses, 2 nurse assistants, and Head of Nursing Division. The triangulation informants were 1 Head and 1 staff of RT and IPS RS. Data were collected by in-depth interview and observation techniques.The results of research showed that human resources factor in laundry management was lacking, the infrastructure was available but was not working properly. Guidelines and SPOs were available but the used of PPE was lacking. Linen planning had not run well. In the execution was not been running properly because linen maintenance, recording and reporting was not in accordance with the should, the linen identification and inventory control was not run well. Linen output still contained stain spots of 10%, thin fabric fiber of 5%, and there is still a delay of linen availability of 5% because the number of linen was not up to standart.Sugesstion for management was to increase the number and capability of human resources, the maintenance of infrastructure to increase the value of use, and good planning for the lack of linen can be fulfilled and done the sorting so that the linen that had stain spots not circulating anymore in the room.